Burp or treat...smell my feet! - Krulik, Nancy E.; Blecha, Aaron (New York, New York : Grosset & Dunlap, an imprint of Penguin Group (USA) LLC, 2014)
George is ready for candy and fun--but dealing with a prank-pulling phantom and learning that his friend might move away is almost as terrifying as the super burp. There are definitely more tricks than treats in store for George when those magic burps take over. Join George as he tries to solve the mystery and keep his friends together!
"Super special"--Front cover.
Keywords: Halloween -- Juvenile fiction; Friendship -- Juvenile fiction; Moving, Household -- Juvenile fiction; Halloween -- Fiction; Friendship -- Fiction; Moving, Household -- Fiction; Mystery and detective stories; Humorous stories